Stdying the origin of oppression according to Freud's vision - ahmed messoud, khadidja (Journal of Social Sciences and Humanities, 2023)
This article studies the nature of repression in society, but before that we had to take into account Freud's study of the origins of repression focusing on its historical and social nature. And to do this, we made use of his writings in order to show that organized repression has, according to Freud, an important role in the development and evolution of societies, and this consists in enabling man to cope with his life in society, and towards the end of the article we revealed the mechanisms of repression which represent the possible conditions of civilization and its continuity, and such mechanisms are not of ideological nature only for they are related to psychological life are well.